On the value and limitations of financial accounting* - BENSTON, GEORGE J. (Contemporary Accounting Research, 1984)
Abstract. Accounting as a means to an end, rather than as an end in itself, is the basic concept on which this essay is based. The ends that accounting serves are control, information for decisions, and an overview, or conspectus, of the enterprise. For these purposes, traditional, transactions‐based accounts are useful, because they yield trustworthy reports of resource flows into and out of an enterprise. Government intervention has emphasized and extended the inherent and cost‐determined limitations of traditional accounting. Though such critics as Professor Chambers are upset at this situation, they have not shown how or which change would be beneficial, net of costs, to users. Exit values, in particular, are not the philosopher's stone that Professor Chambers seeks. As this essay shows, neither these nor other measures of economic values fulfill Professor Chambers' demands. Though traditional accounting has its limitations, they are debilitating only when one holds unrealistic expectations. While I doubt that the benefits from changes such as those suggested by Professor Chambers would exceed their costs, this is an empirical question on which research would be desirable. Résumé. Cet essai se base sur le concept fondamental selon lequel la comptabilité constitue un moyen pour arriver à une fin, plutôt qu'une fin en soi. Assurer le contrôle, fournir des informations pour la prise de décisions et donner un aperçu général ou vue d'ensemble, de l'entreprise, telles sont les fins de la comptabilité. A ces fins, les comptes traditionnels basés sur les opérations s'avèrent utiles parce qu'ils fournissent des rapports fidèles des flux internes et externes des ressources d'une entreprise. L'intervention gouvernementale a souligné et accentué les lacunes reliées aux coûts inhérents à la comptabilité traditionnelle. Bien que des critiques telle celle du professeur Chambers s'offusquent de cette situation, elles n'ont pas encore démontré comment ou quel changement serait profitable, déduction faite des coûts, aux usagers. Les valeurs de sortie, en particulier, ne représentent pas la pierre philosophale que cherche le professeur Chambers. Comme le révèle cet essai, aucune mesure des valeurs économiques ne satisfait les exigences du professeur Chambers. Quoique la comptabilité traditionnelle ait ses limites, elles ne s'avèrent embarassantes que lorsque notre attente est irréaliste. Même si je doute que les avantages des changements suggérés par le professeur Chambers puissent dépasser leurs coûts, on soulève ici un problème empirique pour lequel des recherches seraient souhaitables.